Gene expression profiling associated with the progression to poorly differentiated thyroid carcinomas - Pita, Jaime Miguel Gomes (2009)
BACKGROUND: Poorly differentiated thyroid carcinomas (PDTC) represent a heterogeneous, aggressive entity, presenting features that suggest a progression from well-differentiated carcinomas. To elucidate the mechanisms underlying such progression and identify novel therapeutic targets, we assessed the genome-wide expression in normal and tumour thyroid tissues. METHODS: Microarray analyses of 24 thyroid carcinomas - 7 classic papillary, 8 follicular variants of papillary (fvPTC), 4 follicular (FTC) and 5 PDTC - were performed and correlated with RAS, BRAF, RET/PTC and PAX8-PPARG alterations. Selected genes were validated by quantitative RT-PCR in an independent set of 28 thyroid tumours. RESULTS: Unsupervised analyses showed that gene expression similarity was higher between PDTC and fvPTC, particularly for tumours harbouring RAS mutations. Poorly differentiated thyroid carcinomas presented molecular signatures related to cell proliferation, poor prognosis, spindle assembly checkpoint and cell adhesion. Compared with normal tissues, PTC had 307 out of 494 (60%) genes over-expressed, FTC had 137 out of 171 (80%) genes under-expressed, whereas PDTC had 92 out of 107 (86%) genes under-expressed, suggesting that gene downregulation is involved in tumour dedifferentiation. Significant UHRF1 and ITIH5 deregulated gene expression in PDTC, relatively to normal tissues, was confirmed by quantitative RT-PCR. CONCLUSION: Our findings suggest that fvPTC are possible precursors of PDTC. Furthermore, UHRF1 and ITIH5 have a potential therapeutic/prognostic value for aggressive thyroid tumours. British Journal of Cancer (2009) 101, 1782-1791. doi: 10.1038/sj.bjc.6605340 www.bjcancer.com Published online 6 October 2009 (C) 2009 Cancer Research UK